Value of 3D Preoperative Planning for Primary Total Hip Arthroplasty Based on Biplanar Weightbearing Radiographs. (10th March 2019) - Knafo, Y.; Houfani, F.; Zaharia, B.; Egrise, F.; Clerc-Urmès, I.; Mainard, D.
Abstract : Two-dimensional (2D) planning on standard radiographs for total hip arthroplasty may not be sufficiently accurate to predict implant sizing or restore leg length and femoral offset, whereas 3D planning avoids magnification and projection errors. Furthermore, weightbearing measures are not available with computed tomography (CT) and leg length and offset are rarely checked postoperatively using any imaging modality. Navigation can usually achieve a surgical plan precisely, but the choice of that plan remains key, which is best guided by preoperative planning. The study objectives were therefore to (1) evaluate the accuracy of stem/cup size prediction using dedicated 3D planning software based on biplanar radiographic imaging under weightbearing and (2) compare the preplanned leg length and femoral offset with the postoperative result. This single-centre, single-surgeon prospective study consisted of a cohort of 33 patients operated on over 24 months. The routine clinical workflow consisted of preoperative biplanar weightbearing imaging, 3D surgical planning, navigated surgery to execute the plan, and postoperative biplanar imaging to verify the radiological outcomes in 3D weightbearing. 3D planning was performed with the dedicated hipEOS® planning software to determine stem and cup size and position, plus 3D anatomical and functional parameters, in particular variations in leg length and femoral offset. Component size planning accuracy was 94% (31/33) within one size for the femoral stem and 100% (33/33) within one size for the acetabular cup. There were no significant differences between planned versus implanted femoral stem size or planned versus measured changes in leg length or offset. Cup size did differ significantly, tending towards implanting one size larger when there was a difference. Biplanar radiographs plus hipEOS planning software showed good reliability for predicting implant size, leg length, and femoral offset and postoperatively provided a check on the navigated surgery. Compared to previous studies, the predictive results were better than 2D planning on conventional radiography and equal to 3D planning on CT images, with lower radiation dose, and in the weightbearing position.